A Longitudinal Study of Depressive Symptoms, Neuropsychological Functioning, and Medical Responsibility in Youth With Spina Bifida: Examining Direct and Mediating Pathways. (10th February 2018) - Stern, Alexa; Driscoll, Colleen F Bechtel; Ohanian, Diana; Holmbeck, Grayson N
Abstract: Objective: Given the increased risk for cognitive deficits and development of depressive symptoms in youth with spina bifida (SB), this study aimed to examine two pathways through which depressive symptoms and neuropsychological dysfunction may be associated with medical autonomy in this population: (1) depressive symptoms as predictors of medical autonomy as mediated by attention/executive functioning (the cognitive scarring model), and (2) attention/executive functioning as predictors of medical autonomy as mediated by depressive symptoms (the cognitive vulnerability model). Methods: Participants were recruited as part of a larger, longitudinal study, and included 114 youth with SB ( M age = 10.96 at Time 1), their parents, and teachers. Neuropsychological constructs included attention, working memory, and planning/organizing abilities, which were measured with questionnaire and performance-based data. Depressive symptoms and medical responsibility were assessed via questionnaires from multiple respondents. Results: Bootstrapped mediation analyses revealed that teacher-reported depressive symptoms significantly mediated the relations between neuropsychological functioning (i.e., attention and working memory) and medical responsibility (all p' s < .05); neuropsychological dysfunction did not mediate the relationship between depressive symptoms and medical responsibility. Conclusions: One way in which neurocognitive dysfunction may hinder the development of medical autonomy in youth with SB is through an increased risk for depressive symptoms.